Sustainable Hunting Strategy of Sika Deer (Cervus nippon) in the Neolithic Lower Yangtze River Region, China - Zhang, Ying; Sun, Guoping; Wang, Yonglei; Huang, Yunping; Kikuchi, Hiroki; Yang, Xiaoyan (Frontiers in Earth Science, 2022)
Zooarchaeology studies the human-animal interactions over long periods, and can be used to evaluate the sustainable exploitation of animal resources. Sika deer (Cervus nippon), a Class Ⅰ protected wild animal species of China, used to be commonly found at Neolithic sites across China. In the Yangtze River region, although the Neolithic faunal assemblages show diversity in deer species, sika deer has always been one of the most important components. This research aims at discussing the exploitation of the environmental resources via the hunting strategy of sika deer at Tianluoshan, a Neolithic site in the lower Yangtze River region. The cull pattern and sex ratio of sika deer are reconstructed to display the pattern of prey selection. The results show a specific pattern targeting larger individuals including adults and juveniles, and targeting male over female. This pattern is able to maximize the yield, and keep the deer population sustainable. The sustainable hunting of Sika deer probably is why the Tianluoshan site lasted for nearly a thousand years, during which sika deer had been a major prey for meat.